Are there optimal multiple reserve requirements? - Marco Espinosa; Steven Russell (Federal Reserve Bank of Atlanta, 1996)
A number of developing countries have adopted deficit-finance regimes involving multiple reserve requirements. One question the previous literature on this phenomenon has not addressed is whether multiple-reserves regimes can improve on regimes involving single-currency-reserve requirements if the policy settings of the latter regimes are assumed to be chosen optimally. We find that a "conventional" multiple-reserves regime–a regime with positive nominal rates on reservable bonds–cannot Pareto-improve an optimal single-currency-regime but can, in some cases, increase social welfare over such a regime.
Keywords: 330; Banks and banking; Central; Bank reserves